Breast cancer stem cell antigens as targets for immunotherapy. (February 2020) - Quaglino, Elena; Conti, Laura; Cavallo, Federica
Graphical abstract: Highlights: Cancer stem cells (CSC) are involved in tumor resistance, recurrence and metastasis. CSC targeting is required for tumor eradication. Immunotherapy is a possible approach to CSC elimination. Antigens crucial for CSC maintenance and function are ideal targets. Abstract: The great success of immunotherapy is paving the way for a new era in cancer treatment and is driving major improvements in the therapy of patients suffering from a range of solid tumors. However, the choice of the appropriate tumor antigens to be targeted with cancer vaccines and T-cell therapies is still a challenge. Most antigens targeted so far have been identified on the tumor bulk and are expressed on differentiated cancer cells. The discovery of a small population of cancer stem cells (CSC), which is refractory to most current therapies and responsible for the development of metastasis and recurrence, has made it clear that the ideal targets for immunotherapies are the antigens that are expressed in CSC and play a key role in their function. Indeed, their immunotargeting would enable the eradication of CSC to be performed, thus eliminating the tumor source. We call these antigens "CSC oncoantigens". Herein, we summarize the controversial nature of breast CSC, discuss why they represent good candidates for cancer immunotherapy, and review the CSC antigens that have been used as targets for CSC immunotargeting this far. Moreover, we describe the pipeline that we have developed for the identification of fresh CSC oncoantigens, and present the pre-clinical results obtained with vaccines that target some of these antigens.